Elastic-plastic stress analysis in aluminum metal-matrix composite-laminated plates ([0°/?°]2) under transverse uniformly distributed load - Arslan, N; Kaman, MO; Duranay, M (Sage Publications Ltd, 2004)
In this paper, an elastic-plastic stress analysis is carried out in unidirectional reinforced steel-aluminum composite-laminated plates under transverse loading and simply supported conditions. For the elastic-plastic stress analysis, the mathematical formulation is given for small deformations. Finite Element Method and first-order shear deformation theory are used. A finite element computer program is developed for stress analysis. The laminated plates of constant thickness are manufactured by stacking four layers bonded symmetrically or anti symmetrically. The residual stress components and yield points are calculated for each layer and compared with different reinforced layers. The location and the expansion of the plastic zones are obtained according to loading gradually increased from yield point as 0.0001 MPa at each load step. The load capacity of the laminated plate increases by means of the residual stresses.
Keywords: residual stress; plastic zone; metal-matrix-laminated composite; elasto-plastic stress analysis; finite element method